Bacteria in the adventitia of cardiovascular disease patients with and without rheumatoid arthritis. - Samuel A Curran (Public Library of Science (PLoS), 2014)
The incidence of atherosclerosis is significantly increased in rheumatoid arthritis (RA). Infection is one factor that may be involved in the pathogenesis of both diseases. The cause of RA and atherosclerosis is unknown, and infection is one of the factors that may be involved in the pathogenesis of both diseases. The aims of this study were to identify bacteria in the aortic adventitia of patients with cardiovascular disease (CVD) in the presence and absence of RA, and to determine the effect of identified candidate pathogens on Toll-like receptor (TLR)-dependent signalling and the proinflammatory response. The aortic adventitia of 11 CVD patients with RA (RA+CVD) and 11 CVD patients without RA (CVD) were collected during coronary artery bypass graft surgery. Bacteria were detected in four samples from CVD patients and three samples from RA+CVD patients and identified by 16S rRNA gene sequencing. Methylobacterium oryzae was identified in all three RA+CVD samples, representing 44.1% of the bacterial flora. The effect of M. oryzae on TLR-dependent signalling was determined by transfection of HEK-293 cells. Although mild TLR2 signalling was observed, TLR4 was insensitive to M. oryzae. Human primary macrophages were infected with M. oryzae, and a TLDA qPCR array targeting 90 genes involved in inflammation and immune regulation was used to profile the transcriptional response. A significant proinflammatory response was observed, with many of the up-regulated genes encoding proinflammatory cytokines (IL-1α, IL-1β, IL-6, TNF-α) and chemokines (CCR7, IL-8). The aortic adventitia of CVD patients contains a wide range of bacterial species, and the bacterial flora is significantly less diverse in RA+CVD than CVD patients. M. oryzae may stimulate an proinflammatory response that may aggravate and perpetuate the pathological processes underlying atherosclerosis in RA patients.